The Effect of Syndesmosis Screw Removal on the Reduction of the Distal Tibiofibular Joint: A Prospective Radiographic Study. (June 2014) - Song, Daniel J.; Lanzi, Joseph T.; Groth, Adam T.; Drake, Matthew; Orchowski, Joseph R.; Shaha, Steven H.; Lindell, Kenneth K.
Background: Injury to the tibiofibular syndesmosis is frequent with rotational ankle injuries. Multiple studies have shown a high rate of syndesmotic malreduction with the placement of syndesmotic screws. There are no studies evaluating the reduction or malreduction of the syndesmosis after syndesmotic screw removal. The purpose of this study was to prospectively evaluate syndesmotic reduction with CT scans and to determine the effect of screw removal on the malreduced syndesmosis. Methods: This was an IRB-approved prospective radiographic study. Patients over 18 years of age treated at 1 institution between August 2008 and December 2011 with intraoperative evidence of syndesmotic disruption were enrolled. Postoperative CT scans were obtained of bilateral ankles within 2 weeks of operative fixation. Syndesmotic screws were removed after 3 months, and a second CT scan was then obtained 30 days after screw removal. Using axial CT images, syndesmotic reduction was evaluated compared to the contralateral uninjured ankle. Twenty-five patients were enrolled in this prospective study. The average age was 25.7 (range, 19 to 35), with 3 females and 22 males. Results: Nine patients (36%) had evidence of tibiofibular syndesmosis malreduction on their initial postoperative axial CT scans. In the postsyndesmosis screw removal CT scan, 8 of 9 or 89% of malreductions showed adequate reduction of the tibiofibular syndesmosis. There was a statistically significant reduction in syndesmotic malreductions ( t = 3.333, P < .001) between the initial rate of malreduction after screw placement of 36% (9/25) and the rate of malreduction after all screws were removed of 4% (1/25). Conclusions: Despite a high rate of initial malreduction (36%) after syndesmosis screw placement, 89% of the malreduced syndesmoses spontaneously reduced after screw removal. Syndesmotic screw removal may be advantageous to achieve final anatomic reduction of the distal tibiofibular joint, and we recommend it for the malreduced syndesmosis. Level of Evidence: Level IV, prognostic case series.